A Rare Mutation in SMAD9 Associated With High Bone Mass Identifies the SMAD‐Dependent BMP Signaling Pathway as a Potential Anabolic Target for Osteoporosis. (14th November 2019) - Gregson, Celia L; Bergen, Dylan J. M.; Leo, Paul; Sessions, Richard B; Wheeler, Lawrie; Hartley, April; Youlten, Scott; Croucher, Peter I; McInerney‐Leo, Aideen M; Fraser, William; Tang, Jonathan CY; Anderson, Lisa; et al.
ABSTRACT: Novel anabolic drug targets are needed to treat osteoporosis. Having established a large national cohort with unexplained high bone mass (HBM), we aimed to identify a novel monogenic cause of HBM and provide insight into a regulatory pathway potentially amenable to therapeutic intervention. We investigated a pedigree with unexplained HBM in whom previous sequencing had excluded known causes of monogenic HBM. Whole exome sequencing identified a rare (minor allele frequency 0.0023), highly evolutionarily conserved missense mutation in SMAD9 (c.65T>C, p.Leu22Pro) segregating with HBM in this autosomal dominant family. The same mutation was identified in another two unrelated individuals both with HBM. In silico protein modeling predicts the mutation severely disrupts the MH1 DNA‐binding domain of SMAD9. Affected individuals have bone mineral density (BMD) Z ‐scores +3 to +5, mandible enlargement, a broad frame, torus palatinus/mandibularis, pes planus, increased shoe size, and a tendency to sink when swimming. Peripheral quantitative computed tomography (pQCT) measurement demonstrates increased trabecular volumetric BMD and increased cortical thickness conferring greater predicted bone strength; bone turnover markers are low/normal. Notably, fractures and nerve compression are not found. Both genome‐wide and gene‐based association testing involving estimated BMD measured at the heel in 362, 924 white British subjects from the UK Biobank Study showed strong associations with SMAD9 (PGWAS = 6 × 10 −16 ; PGENE = 8 × 10 −17 ). Furthermore, we found Smad9 to be highly expressed in both murine cortical bone–derived osteocytes and skeletal elements of zebrafish larvae. Our findings support SMAD9 as a novel HBM gene and a potential novel osteoanabolic target for osteoporosis therapeutics. SMAD9 is thought to inhibit bone morphogenetic protein (BMP)‐dependent target gene transcription to reduce osteoblast activity. Thus, we hypothesize SMAD9 c.65T>C is a loss‐of‐function mutation reducing BMP inhibition. Lowering SMAD9 as a potential novel anabolic mechanism for osteoporosis therapeutics warrants further investigation. © 2019 The Authors. Journal of Bone and Mineral Research published by American Society for Bone and Mineral Research.